2016
DOI: 10.1017/s1047951116000238
|View full text |Cite
|
Sign up to set email alerts
|

Role of anxiety and depression in adolescents with chest pain referred to a cardiology clinic

Abstract: Chest pain during teenage is more prevalent, but not risky. Undergoing a detailed history and full physical examination can help diagnose the causes in the majority of cases. Given the prevalence of a psychological group as well as role of anxiety and depression in most patients, referring to a psychiatrist is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…This finding was consistent with the expectations, suggesting that high anxiety level is a significant risk factor for the development of UCP [7,9,10]; and UCP itself may cause enormous anxiety [12] and negative perception of self [40] and depressive symptoms [8]. Interestingly, the parental SDQ failed to provide sufficient information about emotional problems of the adolescents.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding was consistent with the expectations, suggesting that high anxiety level is a significant risk factor for the development of UCP [7,9,10]; and UCP itself may cause enormous anxiety [12] and negative perception of self [40] and depressive symptoms [8]. Interestingly, the parental SDQ failed to provide sufficient information about emotional problems of the adolescents.…”
Section: Discussionsupporting
confidence: 81%
“…High anxiety [8,9] and depression levels [9,10], hypervigilance to the physical sensations and excessive body monitoring [11] may increase the risk of UCP. Although chest pain is rarely caused by cardiac reasons, it still creates significant anxiety because of the potential consequences such as sudden death [12].…”
Section: Introductionmentioning
confidence: 99%
“…As for anxiety and depression in patients, previous studies have been conducted in different diseases and different populations. Studies have shown that patients with coronary heart disease, asthma, chest pain and other diseases may have obvious anxiety and depression problems . Anxiety is associated with sex, age, pain intensity and pain treatment, while depression is associated with gender, pain intensity and duration of treatment, according to a study of psychological problems in patients with chronic pain .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that anxiety is associated with nearly half of the cases presenting with non-cardiac chest pain, while depression is less commonly seen [18]. [19]. In another study, 100 adolescent patients with non-cardiac chest pain were compared with the control group and anxiety, depression and suicidal ideation were significantly higher in the patient group [20].…”
Section: Discussionmentioning
confidence: 95%